The Other Side of the Sky : A Memoir - Ahmedi, Farah; Ansary, Mir Tamim (New York : Simon Spotlight Entertainment, 2005)
Farah Ahmedi's poignant tale of survival (Chicago Tribune) chronicles her journey from war to peace. /Equal parts tragedy and hope, determination and daring, Ahmedi's memoir delivers a remarkable vivid portrait of her girlhood in Kabul, where the sound of gunfire and the sight of gunfire and the sight of falling bombs shaped her life and stole her family. She herself narrowly escapes death when she steps on a land mine. Eventually the war forces her to flee, first over the mountains to refugee camps across the border and finally to America. Ahmedi proves that even the in the direst circumstances, not only can the human heart endure, it can thrive. Provided by the publisher.
850
Accelerated Reader AR
Keywords: Ahmedi, Farah; Refugees -- United States -- Biography; Refugees -- Afghanistan -- Biography; Land mine victims -- Afghanistan -- Biography; Afghans -- United States -- Biography; Children -- Afghanistan -- Biography